The Mediating Effect of Customer Satisfaction Towards The Relationship Between Online and Offline Service Quality to Customer Loyalty at Uniqlo Indonesia - Gareth Eugene; Jennifer Tjitra Wiryawati (iBuss Management, 2023)
The tighter competition across the fast fashion industries has gathered more attention towards customer loyalty as it could increase profitability for the company. Furthermore, gaining customer loyalty could be obtained through online and offline service quality offered by the company. In addition, many previous studies have shown that customer satisfaction could mediate the relationship between offline service quality and customer loyalty. Thus, the researchers now would like to add another rising popularity variable called online service quality, which ended up with the research of finding the mediation effect of customer satisfaction between online and offline service quality with customer loyalty. The study was conducted for Uniqlo Indonesia customers, and questionnaires were spread through the social media platform to collect data for analysis. Continued with the PLS-SEM method, which was used to assess 56 out of 78 respondents who were eligible to give results for the research. The analysis showed a full positive mediation of customer satisfaction between offline service quality and customer loyalty. On the other hand, online service quality and customer loyalty have direct-only non-mediation by customer satisfaction.  Keywords: Offline service quality, Online service quality, Customer satisfaction, Customer loyalty, Uniqlo Indonesia, Mediation.